Educational Humanism in the society of knowledge - Chanto Espinoza, Carlos Luis (2014)
The humanist paradigm in education reflects the interest of human beings to overcome the gaps that traditional education or other ideologies have left in them. That is why, the recognition of the potential and of individual qualities represents a need that has to be fulfilled and observed by the public sector in order to offer better support to the development and pedagogic consolidation of our society. The contextualization of our educational reality proposes changes of thought and methodology according to the needs of the students. In view of this scenario, it is easy to see and to hear about movements aimed at preparing the students and making them face the context in which they get involved, which represents a challenge in the new society of knowledge that requires concrete actions in the classroom for the benefit of human and integral growth.